Pemetaan Produksi Beras d Kabupaten Lamongan Menggunakan Sistem Informasi Geografis (SIG) - Slamet, Ahmad Haris Hasanuddin; Wulandari, Sekar Ayu; Dhandy, Rahmat; Brillyantina, Septine; Rizqullah, Rafly (Politeknik Negeri Jember, 2023)
Lamongan Regency is known as one of the largest rice producers in East Java with a contribution of 8.76 percent to total rice production in East Java. The use of computer-based technology really supports planning, one of which is mapping. The aim of this research is to map rice production in Lamongan Regency using Geographic Information System (GIS) technology. This research uses spatial data in the form of administrative maps of Lamongan Regency in 2017, sea depth maps in 2018 and rice production data in Lamongan Regency in 2017 and 2019. The results of the research show that rice production in Lamongan Regency is not much different in 2017 and 2019. There are fluctuations in rice production in each sub-district. The largest rice production is in Sugio District while the smallest production is in Paciran District. Factors that influence rice production include the area of ​​rice fields, land characteristics, and Lamongan Regency Government policies. Based on spatial analysis with maps, the largest rice production is in Sugio District because it is lowland with a high level of fertility and has the largest area of ​​rice fields. Meanwhile, the lowest rice production is in the Brondong, Paciran, Solokuro, Kalitengah and Deket sub-districts because the limestone mountains are rocky and areas prone to flooding and have limited rice fields. Apart from that, Paciran, Solokuro and Brondong sub-districts are more prioritized in developing the industrial, tourism and trade sectors